Essay on the Pedagogical Activity of Professor N.A. Umov at the Imperial Moscow University in 1893–1911 - Aleksey A. Yakuta (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. A comprehensive study of the nature and results of the pedagogical activity of Professor of Physics N.A. Umov at the Imperial Moscow University (IMU) in 1893–1911 is necessary to ensure the possibility of recreating a holistic picture of the history of development of physics teaching at Moscow University.